PELATIHAN PEMBUATAN OBAT HERBAL DARI TANAMAN TRADISIONAL DALAM PENCEGAHAN PENYAKIT MULUT DAN KUKU DI KAMPUS IV UNIVERSITAS KHAIRUN - Sri Wahyuni; Muhammad Ade Salim; Sri Utami (LP2M STP Mataram, 2024)
Foot and Mouth Disease (FMD) is currently endemic in Indonesia. FMD is caused by the Foot and Mouth Disease Virus (FMDV), which affects various livestock such as cattle, buffalo, goats, and sheep, as well as wild animals like deer, elephants, and camels. It is classified as an acute disease that spreads rapidly through viral infection and is highly contagious. North Maluku Province currently holds a green zone status for Foot and Mouth Disease (FMD). Campus IV of Khairun University (Unkhair), located in Bangko Hamlet, Bobaneigo Madihutu Village, West Halmahera Regency, North Maluku Province, covers an area of approximately 150 hectares. The majority of cattle breeders on Campus IV are traditional breeders, where management practices for maintenance and health are often still conducted traditionally, with knowledge passed down from older generations of breeders to their successors. In recent years, herbal medicines have gained popularity not only for humans but also among livestock breeders. Community service activities will be conducted in May 2024, involving livestock groups in Bangko Hamlet, Bobaneigo Madihutu Village, West Halmahera Regency, North Maluku Province. Ten participants, including lecturers from the Animal Husbandry Study Program and local breeders, will take part in this initiative. The aim of the community service is to introduce Foot and Mouth Disease to the local community and to provide practical training on making herbal medicine for livestock. The community service activities are well-received and valued by the local breeders. During the service, participants have shown great enthusiasm in engaging with the activities, which range from discussion-based counseling to the practical preparation of herbal medicine for cattle